Evaluation of Potential Drug Interaction in Advanced Phase Tuberculosis Patients at Jember Pulmonary Hospital - Yessy Dilla Aisyah; Shinta Mayasari (Jurnal EduHealth, 2026)
Pulmonary TB is a disease caused by infection from the bacteria Mycobacterium tuberculosis that attacks the lungs. Based on WHO data in Indonesia, the total number of TB cases in 2023 was 1,060,000 cases, the prevalence of TB in the city of Jember was 5,244 cases, and nationally, East Java was in second place based on the estimated incidence of TB with a total of 107,547. From the results of a preliminary study at the Jember Pulmonary Hospital, there were 1,803 cases. This study was to evaluate the interaction of antituberculosis drugs in TB patients at Jember Lung Hospital. The method that will be used by researchers in this study is observation. This type of research is descriptive research with the number of samples used as many as 95 samples using the solvin formula. This study uses random sampling techniques. Data analysis uses univariate analysis, data is displayed in the form of frequency and percentage. Based on the results of the study, the number of men diagnosed with TB was 65%, women were 35%, the results showed that out of 95 tuberculosis patients, 100% of patients experienced potential drug interactions. Based on the severity, major was (65%), moderate was (32%), and minor was (3%), the age range that was more often diagnosed with TB was 17-25, namely 20% and age 55-60 was 28%. Based on the research results that most of the potential drug interactions occur in major interactions. The role of pharmacy in terms of drug interactions is to monitor drug use and regulate drug use scheduling, to avoid drug interactions.